Analisis Harga Pokok Tomat di Kelurahan Kaisabu Baru Kecamatan Sorawolio Kota Baubau - Ferdian Adi Saputra Nasran; Idrus Salam; Ilma Sarimustaqiyma Rianse (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2023)
This research examines the price of tomatoes in Kaisabu Baru Village, Sorawolio District and Baubau City. In Kaisabu Baru Village, Sorawolio District, Baubau City, this research seeks to determine the cost of goods sold for tomatoes and determine what variables are obstacles to tomato production. Data analysis used to answer the first goal is by Break Even Point (BEP) analysis, and the second goal is answered using descriptive statistical analysis such as percentages and averages. The samples in this study were farmers who cultivated tomato plants in Kaisabu Baru Village, Sorawolio District, Baubau City, with as many as 33 people. In the calculation of the sample, the Slovin formula is used. Data is collected by directly interviewing farmers, observing research objects, and recording data already available in related offices. The results of this study show: 1) The total average cost of goods sold by respondents per tomato farm is IDR123,224 / planting season, and the average cost of goods sold per hectare is IDR647,412 / planting season.